Engineering effective decision support technologies new models and applications - Power, Daniel J.; IGI Global (Hershey, Pa. : IGI Global (701 E. Chocolate Avenue, Hershey, Pennsylvania, 17033, USA), 2013)
'This book presents a collection of the latest research in decision management support systems and applies those theoretical considerations to best practices in the field through the use of empirical case studies and an analysis of new models and perspectives in knowledge management'--Provided by publisher.
DSS-CMM: a capability maturity model for DSS development processes / Omar F. El-Gayar, Amit V. Deokar, Jie Tao -- Using systems engineering for the development of decision making support systems (DMSS): an analysis of system development methodologies (SDM) / S. Vallance ... [et al.] -- IDSSE-M: a software system engineering methodology for developing intelligent decision-making support systems / Manuel Mora ... [et al.] -- Ontology engineering the'whats,''whys,' and'hows' of data exchange / J. M. Easton, J. R. Davies, C. Roberts -- Using social network analysis to support collective decision-making process / Simon Buckingham Shum ... [et al.] -- Social media in DMSS system development and management / Daniel E. O'Leary -- Automated diagnosis through ontologies and logical descriptions: the ADONIS approach / Alejandro Rodruez-Gonzez ... [et al.] -- Discrepancies and analogies in artificial intelligence and engineering design approaches in addressing collaborative decision-making / Marija Jankovic, Pascale Zarat-- Decision support for crisis incidents / Daniel J. Power, Roberta M. Roth, Rex Karsten -- Visualization-based decision support systems: an example of regional relationship data / Vicki L. Sauter ... [et al.] -- Strategic development of a decision making support system in a public R&D center / Carlos E. Escobar-Toledo, Htor A. Martez-Berumen -- Understanding organisational decision support maturity: case studies of Irish organisations / Mary Daly, Frederic Adam -- Development and application of a spreadsheet-based spatial decision support system (SDSS) / Dossay Oryspayev, Ramanathan Sugumaran, John DeGroote -- Extended TOPSIS with correlation coefficient of triangular intuitionistic fuzzy sets for multiple attribute group decision making / John P. Robinson, Henry E.C. Amirtharaj -- Hierarchical database model for querying economic network independence distribution / Akinwale Adio Taofiki -- One-dimensional cutting stock optimization with usable leftover: a case of low stock-to-order ratio / Miro Gradisar, Jure Erjavec, Luka Tomat.
Includes bibliographical references.
Also available in print.
Mode of access: World Wide Web.
Description based on title screen (IGI Global, viewed April 17, 2013).
Keywords: Decision support systems; Automated diagnosis; Collaborative decision-making.; Crisis management; Database management; Intelligent DMSS; Social media in DMSS; System development methodologies